Mitonuclear Interactions Produce Diverging Responses to Mild Stress in Drosophila Larvae - Rodríguez, Enrique; Grover Thomas, Finley; Camus, M. Florencia; Lane, Nick (Frontiers in Genetics, 2021)
Mitochondrial function depends on direct interactions between respiratory proteins encoded by genes in two genomes, mitochondrial and nuclear, which evolve in very different ways. Serious incompatibilities between these genomes can have severe effects on development, fitness and viability. The effect of subtle mitonuclear mismatches has received less attention, especially when subject to mild physiological stress. Here, we investigate how two distinct physiological stresses, metabolic stress (high-protein diet) and redox stress (the glutathione precursor N-acetyl cysteine, NAC), affect development time, egg-to-adult viability, and the mitochondrial physiology of Drosophila larvae with an isogenic nuclear background set against three mitochondrial DNA haplotypes: one coevolved (WT) and two slightly mismatched (COX and BAR). Larvae fed the high-protein diet developed faster and had greater viability in all haplotypes. The opposite was true of NAC-fed flies, especially those with the COX haplotype. Unexpectedly, the slightly mismatched BAR larvae developed fastest and were the most viable on both treatments, as well as control diets. These changes in larval development were linked to a shift to complex-I driven mitochondrial respiration in all haplotypes on the high-protein diet. In contrast, NAC increased respiration in COX larvae but drove a shift towards oxidation of proline and succinate. The flux of reactive oxygen species was increased in COX larvae treated with NAC, and was associated with an increase in mitochondrial DNA copy number. Our results support the notion that subtle mitonuclear mismatches can lead to diverging responses to mild physiological stress, undermining fitness in some cases, but surprisingly improving outcomes in other ostensibly mismatched fly lines.